Psychological resilience is linked to motor strength and gait endurance in early multiple sclerosis. (August 2020) - Klineova, Sylvia; Brandstadter, Rachel; Fabian, Michelle T; Sand, Ilana Katz; Krieger, Stephen; Leavitt, Victoria M; Lewis, Christina; Riley, Claire S; Lublin, Fred; Miller, Aaron E; Sumowski, James F
Background: Psychologically resilient persons persist despite obstacles and bounce back after adversity, leading to better outcomes in non-neurologic populations. It is unknown whether psychological resilience relates to objective functional outcomes in multiple sclerosis (MS). Objective: To determine whether psychological resilience explains differential objective cognitive and motor functioning in persons with early MS. Methods: Psychological resilience was assessed in 185 patients with early MS and 50 matched healthy controls with the Connors-Davidson Resilience Scale (CDRS-10). Subjects completed the MS Functional Composite (MSFC) and a comprehensive neurobehavioral evaluation. Correlations assessed links between CDRS-10 and MSFC, motor indices (Total, Fine Motor, Gross Motor), and cognitive indices (Total, Cognitive Efficiency, Memory). Results: Higher CDRS-10 among patients was linked to better MSFC and motor outcomes (but not cognition), with the most robust relationships for gross motor function (grip strength, gait endurance). Findings were independent of mood and fatigue. CDRS-10 was unrelated to MS disease burden. CDRS-10 was also specifically linked to motor outcomes in healthy controls. Conclusion: Functional outcomes vary across persons with MS, even when disease burden and neurologic disability are low. These findings identify high psychological resilience as a non-disease-specific contributor to motor strength and endurance, which may explain differential outcomes across patients.